Sound insulation in Malaysia Buildings. Case studies on Airborne Transmission / Alfian Gunawi - Gunawi, Alfian (Faculty of Architecture, Planning and Surveying, 1988)
Sound is natural phenomenon that happens in the human enviroment.without it the world would be static but if it exceeds its limit it will only be an ear acheing sensation.